2019
DOI: 10.17843/rpmesp.2019.364.4900
|View full text |Cite
|
Sign up to set email alerts
|

Cepillado dental y niveles de flúor en pastas dentales usadas por niños peruanos menores de 12 años

Abstract: Análisis secundario de los datos de 41 330 niños de uno a 11 años de la Encuesta Demográfica y de Salud Familiar (ENDES) 2018. Se reportó la frecuencia de cepillado y el uso de pasta dental según el nivel de flúor (no cepillado, adecuado, inadecuado, no mostró/no usa pasta, e ilegible), según variables socioeconómicas y geográficas. Un 7,8% de los niños evaluados no se cepillaba los dientes, se evidenció diferencias porcentuales significativas (p 0,001) en el uso de pasta dental con concentración inadecuada de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
1
9
0
4
Order By: Relevance
“…This is due to the 2001 Technical Standard that allows commercialization of other concentrations lower than those recommended. 16,19,20 According to data from the Peruvian Cosmetic and Hygiene Association (COPECOH, for its Spanish acronym), developed cities generate a greater demand for oral hygiene products. 21,22 In contrast, in the most vulnerable populations, programs like "Plan de Salud Escolar" and "Juntos" have promoted practices and habits aimed at oral health care mainly among public schools through the delivery of toothpastes and toothbrushes.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the 2001 Technical Standard that allows commercialization of other concentrations lower than those recommended. 16,19,20 According to data from the Peruvian Cosmetic and Hygiene Association (COPECOH, for its Spanish acronym), developed cities generate a greater demand for oral hygiene products. 21,22 In contrast, in the most vulnerable populations, programs like "Plan de Salud Escolar" and "Juntos" have promoted practices and habits aimed at oral health care mainly among public schools through the delivery of toothpastes and toothbrushes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, these have been analyzed in previously published research. 7,8 The databases were extracted from the INEI's official website, through multiple sources of information, and then unified into a single matrix to be analyzed in STATA v. 17 software. This was done using the complex sample module, since it is a national survey with possible representative estimates.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Hernández-Vásquez et al concluded that a considerable fraction of Peruvian children under 12 years of age did not practice toothbrushing, especially those settled in the highlands and urban sectors of Peru; likewise the absence of this habit was observed with greater predominance in those wiofth five years of age or younger. 7 A study applied in the United Arab Emirates showed that children whose day-care centers were located in rural areas had a greater experience of caries and a higher amount of visible plaque compared to other geographical areas; in addition, the same publication established infrequent tooth brushing as a factor associated with the high prevalence of dental caries in that community, 18 which could explain the health conditions of these children.…”
Section: Restmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 At the national level, specific reports indicate a limited frequency of toothbrushing, mainly in younger individuals and members of families with limited economic resources. 12,13 Promoting healthy practices, like toothbrushing, 14 within the context of the lowest dental care access is challenging, especially in vulnerable communities. Scientific evidence shows that the successful establishment of the toothbrushing habit is linked to receiving information on the prevention of oral cavity diseases, which in many countries is provided in the dental office.…”
Section: Introductionmentioning
confidence: 99%